Dropping out in Adult and Youth Education. Stories of abandonment or determination? Practitioners’ uses and tactics to self manage life - Oliveira, Inês Barbosa de; Coutinho, Maria Clara Gama Cabral (Education Policy Analysis Archives, 2013)
Bases on narratives about education by young and adults, this text discuss the idea of understanding drop out as another form of the use of the school more than just a give up or abandonment. Our reflection hypothesis is that these students, which abdicate of giving a continuance of their education, can be leaving school in EJA modality by choice of life, with the rights that they possess of using the school on their own way and to their own benefit, choosing to be in it when there are specific interests on what it can offer, and not to be in it when there are other interests that superpose, without prejudices to their rights to have a good life, in the cognitive justice perspective, where the relationships between the knowledge are horizontal and non hierarchic, evidencing a dialog and an organization of network that do not necessarily privilege the formal knowledge, establishing as an ecological relation, of complementary and interdependence between the school knowledge and the knowledges learnt in everyday life. We think, either, these choices can be understood like ways of exercising the right to learn for life from the point of goals and hierarchy of values to beyond of hegemony, , because it is based on recognition, on validity and by the importance of differents knowledge and values.